Pakistan’s Role in the Shanghai Cooperation Organization (SCO): Strategic Gains or Diplomatic Tokenism - Asifa Zafar; Nasra Batool (Journal of Religion and Society, 2025)
This article examines Pakistan's role in the Shanghai Cooperation Organization (SCO), assessing whether its participation has yielded strategic gains or remains symbolic. Pakistan joined the SCO as a full member in 2017, leveraging the platform to enhance regional connectivity, counterterrorism cooperation, and economic integration, particularly through initiatives like the China-Pakistan Economic Corridor (CPEC). The SCO provides Pakistan with opportunities to diversify its foreign policy, strengthen ties with China and Russia, and address energy security through projects like the TAPI pipeline. However, Pakistan faces significant challenges, including limited influence in SCO decision-making dominated by China and Russia, lack of tangible economic benefits, and persistent tensions with India that hinder multilateral cohesion. The article highlights Pakistan's achievements, such as participation in joint military exercises and contributions to regional stability dialogues, while also addressing criticisms of "diplomatic tokenism" due to its peripheral role in shaping SCO policies. A comparative analysis with India's more assertive SCO engagement further underscores Pakistan's constraints. The study concludes with policy recommendations for Pakistan to maximize its SCO involvement, emphasizing economic integration, conflict resolution, and soft power diplomacy. Keywords: Pakistan, Shanghai Cooperation Organization (SCO), Strategic Gains, Diplomatic Tokenism, China-Pakistan Economic Corridor (CPEC), Regional Connectivity, Counterterrorism, India-Pakistan Tensions, Multilateral Diplomacy, Soft Power